2012
DOI: 10.4236/jcdsa.2012.23026
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Tolerability, Safety and Efficacy of a Pantothenic Acid Based Dietary Supplement in Subjects with Mild to Moderate Facial Acne Blemishes

Abstract: Objective: It has been suggested that pantothenic acid may have antibacterial and skin softening activity. The aim of this study was to explore the feasibility, tolerability, safety and preliminary efficacy of oral administration of a dietary supplement containing pantothenic acid in healthy human males and females with mild to moderate facial acne vulgaris.Methods: An open-label, single arm study of healthy adults who had been previously diagnosed with mild to moderate acne vulgaris was performed. Subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Furthermore, niacinamide regulates skin tone, helps minimise marks on the skin and reduce appearance of hyperpigmentation [52] . Clinical studies using daily oral supplementation containing pantothenic acid in healthy human adults with mild and moderate acne has shown the reduction of total facial acne and blemishes after 8-and 12-weeks respectively versus placebo control [53,54] . A deficiency in Vitamin D (25 hydroxyvitamin D3) was shown to correlate with increased severity of acne lesions, which could be mitigated by supplementation with oral cholecalciferol at 1000 IU/day for 2 months [55] .…”
Section: The Endocrine System and Hormonal Effects On Skin Collagenmentioning
confidence: 99%
“…Furthermore, niacinamide regulates skin tone, helps minimise marks on the skin and reduce appearance of hyperpigmentation [52] . Clinical studies using daily oral supplementation containing pantothenic acid in healthy human adults with mild and moderate acne has shown the reduction of total facial acne and blemishes after 8-and 12-weeks respectively versus placebo control [53,54] . A deficiency in Vitamin D (25 hydroxyvitamin D3) was shown to correlate with increased severity of acne lesions, which could be mitigated by supplementation with oral cholecalciferol at 1000 IU/day for 2 months [55] .…”
Section: The Endocrine System and Hormonal Effects On Skin Collagenmentioning
confidence: 99%
“…There was a significant reduction in lesion count from baseline 20.45 ± 10.44 to 11.18 ± 6.38 after eight weeks of treatment. Sixty percent of subjects reported a marked improvement, and 30% reported slight improvement, while one of the subjects reported no change [ 811 ]. The randomized, double blind placebo-controlled study proved the effectiveness of the same product on reduction of global facial lesions count [ 812 ].…”
Section: Pantothenic Acid—vitamin Bmentioning
confidence: 99%
“…A recent feasibility study has also shown that daily oral supplementation of a nutritional agent containing pantothenic acid for 8 weeks was feasible and safe. Secondary endpoints of that study demonstrated that there was a reduction in total facial acne lesions over the 8-week study period [ 12 ]. Therefore, the purpose of this study was to further test the pantothenic acid-based supplement in a randomized, double-blind, placebo-controlled clinical study to assess the effectiveness of the study agent in reducing global facial lesion count versus placebo over a 12-week study period.…”
Section: Introductionmentioning
confidence: 99%